Peranan Kompetensi Manajerial Kepala Sekolah Dalam Meningkatkan Kedisiplinan Guru di SD Inpres Tompotana Kabupaten Takalar - Hamzah Hamzah; Andi Sugiati; Sitti Fatimah (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to find out the role of the principal's managerial competence in improving teacher discipline. Factors and factors that hinder and support the principal's managerial competence in improving teacher discipline at SD Inpres Tompotana, Takalar Regency. This research was carried out in Takalar, where it was at SD Inpres Tompotana, Takalar Regency, which took place from May 27 2023 to July 27 2023. The method of collecting data in this study used interviews, documentation and observation. The subjects in this study were school principals and teachers. The results of research conducted by researchers, that the role of the principal in improving teacher discipline, as well as the supporting and inhibiting factors of the Principal's Managerial Competence in Improving Teacher Discipline at SD Inpres Tompotana, Takalar Regency. This is very important for teacher independence through various forms of training, namely with the guidance and motivation of the Principal towards the teacher and also from the awareness of the teacher himself in developing the mandate and responsibility as educators who should be an example, a role model for their students, self-discipline training so that Principals, fellow teachers and students can carry out their obligations wholeheartedly, namely arriving on time, being disciplined from various aspects of the school environment so as to create an effective and time-disciplined school. This research uses qualitative research methods.